Blinatumomab added to conditioning regimen of allogeneic hematopoietic stem cell transplantation for adult MRD-positive acute lymphoblastic leukemia: a single-center case series - Hui Fu; Yanmin Zhao; Huarui Fu; Meng Liu; Congxiao Zhang; Li Yang; He Huang; Jimin Shi; Jian Yu (Hematology)
Allogeneic hematopoietic stem cell transplantation (Allo-HSCT) remains the mainstay of treatment for adults with high-risk acute lymphoblastic leukemia (ALL). Due to the crucial role of measurable residual disease (MRD) before Allo-HSCT in predicting relapse and the promising anti-leukemia effect of blinatumomab, we documented a short-course, low-dose conditioning regimen incorporating blinatumomab for Allo-HSCT in three ALL patients with positive MRD. Following the administration of the blinatumomab-containing conditioning regimen, all patients attained complete remission (CR) with negative MRD status, and no severe adverse events were observed. After a 2-year follow-up, 2/3 of patients remained disease-free and attained long-term survival following transplantation. These cases indicated a short-term blinatumomab conditioning regimen may effectively prolong patient survival, improve prognosis, and offer a safe and cost-effective treatment for high-risk ALL patients with positive MRD. The addition of blinatumomab to the conditioning regimen of Allo-HSCT is feasible for high-risk ALL patients with positive MRD.